Fibrinolytic Activity and Dose-Dependent Effect of Incubating Human Blood Clots in Caffeic Acid Phenethyl Ester: In Vitro Assays - Elnager, Abuzar; Hassan, Rosline; Idris, Zamzuri; Mustafa, Zulkifli; Arfah, Nadiah Wan; Sulaiman, S. A.; Siew, Hua Gan; Abdullah, Wan Zaidah (Hindawi Publishing Corporation, 2015)
Background. Caffeic acid phenethyl ester (CAPE) has been reported to possess time-dependent fibrinolytic activity by in vitro assay. This study is aimed at investigating fibrinolytic dose-dependent activity of CAPE using in vitro assays. Methods. Standardized human whole blood (WB) clots were incubated in either blank controls or different concentrations of CAPE (3.75, 7.50, 15.00, 22.50, and 30.00mM). After 3 hours, D-dimer (DD) levels and WB clot weights were measured for each concentration. Thromboelastography (TEG) parameters were recorded following CAPE incubation, and fibrin morphology was examined under a confocal microscope. Results. Overall, mean DD (